Evaluation of normal range of mouth opening using three finger index: South India perspective study - Jayshree Agrawal; Prashanth K Shenai; Laxmikanth Chatra; Pavan Y Kumar (Wolters Kluwer Medknow Publications, 2015)
Aims: The frequency, with which restricted mouth opening is encountered in the clinical practice, makes it essential to establish what constitutes the normal range. This study was undertaken to evaluate the normal range of mouth opening in adult population in south India. Settings and Design: randomized clinical study conducted on dentate adult patients to evaluate the normal range of mouth openin. Materials and Methods: 500 healthy patients aged between 18-59 were randomly selected and divided into four groups according to their age ranges. The maximum inter-incisal distance and width of right and left three fingers at the first distal inter-phalanges were measured using vernier calipers. Statistical analysis used: ANOVA test, student t test and pearsons correlation test. Results: The mean value and range of maximum mouth opening of 50.3mm±6.26mm for males and 49.9mm±6.74mm for females was recorded. These values were significant and correlated with the width of three fingers. It was found that the greatest mean maximum mouth opening was recorded in youngest age group and lowest was recorded in older age group in both genders. Conclusions: The mean mouth opening value decreases with age and is lesser in females as compared to males of same age. This study demonstrated that individuals in all the four groups were able to vertically align their right and left three fingers between the upper and lower central incisors upto the first distal interphalangeal folds thus suggesting that, width of three fingers can be used as 'tool' to distinguish 'normal' from 'restricted' mouth opening.